Healthcare Provider Perspectives on Access to Healthcare for Chronic Low Back Pain Across Urban, Rural, and Remote Settings - Katie Crockett; Stacey Lovo; Alison Irvine; Catherine Trask; Sarah Oosman; Veronica McKinney; Terrence McDonald; Nazmi Sari; Rosmary Martinez-Rueda; Harini Aiyer; Bertha Carnegie; Marie Custer; et al. (SAGE Publishing, 2024)
Introduction: Chronic low back pain (CLBP) is a debilitating condition that affects millions of people worldwide. Healthcare providers play a crucial role in improving access to care for patients with CLBP, but they face numerous challenges in doing so. This study focuses on healthcare provider perspectives of CLBP healthcare access. Methods: Semi-structured interviews were conducted with 16 healthcare providers across a variety of disciplines who care for people with CLBP across Saskatchewan, Canada. A qualitative interpretive research approach with inductive thematic analysis was employed. Results: Years of experience ranged from 1 to >20 years. Participants represented 11 disciplines across urban, rural, and/or remote settings. Four overarching themes were identified: (1) Challenges for healthcare providers; (2) Anticipating and recognizing barriers and consequences for patients; (3) Facilitators for healthcare providers and patients; (4) Recommendations on improving accessibility to healthcare. Several barriers were identified for healthcare providers to provide optimal, evidence-based care across Saskatchewan, including patient complexity and past experiences, access to resources and coordinating care. Healthcare providers recognized barriers for patients, which ultimately influenced healthcare provider decisions and care provision. Coordinated care and funding were identified as facilitators that support healthcare provider recommendations of multidisciplinary care and improving provider education to enhance provision of care for chronic low back pain. Conclusion: Future care models should build on these identified factors, while considering clinical and community-specific contexts.